(3efgLjI GdHMK aj GdYdhe GdGLJeGYjI h GdGOGQjI (B:s (3GdeaGgje h GdCOhGJ (B/s - (3GdYSGa, CMeO YGQas; (3GdhGOj, eMehO s ((3YeGf(B: s (3OGQ UaGA ddfTQ hGdJhRjY(B, s, 2011)
(3eONd Edi GdHMK GdYdej h efGgL h CSGdjH GdHMhK GdYdejI, GNJjGQ eTcdI GdHMK h UjGZJgG, OQGSI GdaQVjI, YjfI GdHMK CfhGYgG h WQb GNJjGQgG h JUejegG, hSGFd h GOhGJ LeY GdHjGfGJ dCZQGV GdHMK, YQV h JMdjd GdHjGfGJ GdGMUGFjI, GdNWI GdJMVjQjI ddHMK GdYdej JVe JfXje cJGHI GdHMK GdYdej , JhKjb eUGOQ GdeYdheGJ aj GdHMK GdYdej h CNjQG hGbY GdHMK GdYdej aj GdhWf GdYQHj eY ETGQI Gdi GdCQOfs
Keywords: (3GdCSGdjH GdEOGQjI, HMKs; (3GdHMKs; (3WQb GdHMKs